2006
DOI: 10.1017/s0950268806007539
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant capacity of plasma in asymptomatic carrier state ofNeisseria meningitidis

Abstract: Reduction of the antioxidant capacity of plasma has been linked with the impairment of an effective immune response and so we hypothesized that the carriage rate of Neisseria meningitidis in asymptomatic subjects might correlate with the levels of antioxidants in plasma. To this end we took pharyngeal swabs from 339 children in Marquesado Basic Health Zone, Granada, Spain and in addition determined the total antioxidant capacity (TAC) in plasma samples from these subjects. The overall prevalence of N. meningit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, at high temperatures, oxidative stress increases, and antioxidants become scarce. Cellular oxidative stress is associated with impairment of host immunity, and immune responsiveness has been found to correlate with levels of antioxidants in plasma in carriers of N meningitidis , particularly in children less than 3 years of age 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at high temperatures, oxidative stress increases, and antioxidants become scarce. Cellular oxidative stress is associated with impairment of host immunity, and immune responsiveness has been found to correlate with levels of antioxidants in plasma in carriers of N meningitidis , particularly in children less than 3 years of age 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…Serum TACs (measured by TRAP) of sepsis patients are higher than those of healthy controls and correlated with clinical score [ 21 ]. Plasma TAC (measured by the corcin bleaching method) of asymptomatic carrier of Neisseria meningtidis was lower than those of healthy control children [ 22 ]. Serum TAC (ABTS· + decolorization method) of hypertension patients was lower than controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In this sense, an increase in the TAC of saliva could produce modifications in the adherence of Streptococcus to the den tal plaque and lead to greater cariogenic activity. Several authors 16 have reported greater activity in prooxidant molecules such as nitric oxide (NO) in the saliva of subjects with dental caries.…”
Section: Discussionmentioning
confidence: 99%